Організація обліку операцій із цінними паперами власної емісії: теоретичні аспекти - Мелень, Олена Валентинівна; Побережна, Наталія Миколаївна; Стригуль, Лариса Станіславівна (My University, 2019)
У статті досліджено особливості організації операцій з обліку цінних паперів власної емісії, їх класифікація, первинне розміщення та викуп, а також розглянуто документальне оформлення операцій із цінними паперами. Важливим об'єктом в організації обліку операцій із цінними паперами є облікова політика підприємства. Для повного відображення всіх операцій із цінними паперами в обліку і фінансовій звітності доцільно виділити такі складники: економічно обґрунтована класифікація цінних паперів; порядок емісії та відображення витрат, пов'язаних з емісією; своєчасне та повне документування емісії та обігу цінних паперів; методи оцінки і відображення цінних паперів на рахунках бухгалтерського обліку та у фінансовій звітності підприємства; визначення терміну утримання цінних паперів; методичні рекомендації щодо проведення інвентаризації цінних паперів; методичні підходи до обліку доходів і витрат за операціями із цінними паперами.

The article deals with the peculiarities of the organization of operations for the accounting of own emission securities issuance, their classification, initial placement and redemption, as well as documenting the transactions with securities issuance. The organization of accounting for securities issuance transactions covers the process from the initial registration of economic information to the reporting. An important objective in accounting for securities issuance transactions is the accounting policy of the enterprise. It is advisable to distinguish the following components: economically justified classification of securities; the procedure for issuing and displaying the costs associated with the issue; timely and complete documentation of the issuance and circulation of securities; methods of valuation and reflection of securities in the accounts of the company and in the financial statements; determination of the term of securities holding; methodical recommendations for the inventory; methodical approaches to accounting of incomes and expenses on operations with securities. The basis of accounting for financial investments is an economically justified classification, which, by the term of investment, divides financial investments into current, long-term and indefinite. The term of investment of securities issuances on their rating. All current financial investments are carried at fair value at the balance sheet date. In practice, it is identified with the market value of investments. The value of investments at the date of the balance sheet is different from the initial valuation. Financial investments, the fair value of which can not be reliably determined, are stated at the balance sheet date at their cost, taking into account the decrease in the value of the investment. The cost of a financial investment may be higher or lower than fair value. In this case, financial investments are subject to overestimation. The estimation of perpetual financial investments depends on the type of securities and on the level of influence of the investor on the operational and financial activity of the enterprise. The companies must necessarily check and document the availability of financial investments, determine their compliance with the criteria established in the National accounting position. An important task of organizing accounting for securities issuance transactions is the organization of their primary, current and final records. The reflection in the accounting of transactions from the initial placement of securities issuance is regulated by the norms of the Tax Code of Ukraine.
Organization of accounting for operations of own securities issuance: theoretical aspects
Keywords: фінансова інвестиція; емісія; цінні папери; акції; облігації; financial investment; issue; securities issuance; stocks; bonds